Sectoral Public Expenditure and Income Inequality in Indonesia: A Spatial Panel Approach - Ita Pingkan Fasnie Rorong; Tri Oldy Rotinsulu; Dennij Mandeij; Muhammad Ridwan Manulusi; Angela Nirmala Maria Lumi (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2026)
Purpose – This study evaluated the impact of sectoral local government expenditures (economic, health, education, and social protection) on regional income inequality. To address the specification bias inherent in traditional frameworks, this research explicitly accommodated spatial spillover mechanisms. Design/methodology/approach – The empirical analysis utilized a balanced macro-level panel dataset comprising 33 Indonesian provinces, yielding 495 observations over a 15-year observation period from 2010 to 2024. A Spatial Durbin Model accommodated unobserved individual heterogeneity while simultaneously capturing endogenous spatial interactions. Marginal policy impacts were extracted via Monte Carlo parametric bootstrap simulations. Finding/Results – A positive spatial autoregressive parameter confirmed that income inequality in one province systematically influenced contiguous territories. Decomposing the marginal impacts revealed that local educational expenditures directly compressed internal income inequality. Conversely, health allocations exhibited a positive direct effect on the Gini ratio. Furthermore, localized economic expenditures generated negative spatial spillovers that significantly reduced income disparities across neighboring provinces. Originality/Value – Policymakers must transition from isolated fiscal planning toward coordinated interregional public investments to leverage positive agglomeration externalities. Physical infrastructure expansion requires harmonization with targeted social protection frameworks. Future research should integrate intra-regional microdata and explore the nonlinear threshold effects of fiscal decentralization to refine territorial wealth redistribution strategies.